Dental Injuries in a Sample of Portuguese Militaries – A Preliminary Research. Issue 11 (23rd May 2018) - Azevedo, Luís; Martins, David; Veiga, Nélio; Fine, Peter; Correia, André
Abstract: Introduction: Traumatic dental and maxillofacial injuries are very common and appear to affect approximately 20–30% of permanent dentition, with often serious psychological, economic, functional, and esthetic consequences. Militaries are a highest risk group for orofacial trauma, not only because they are constantly engaged in physical activity (which increase the risk of traumatic injuries) but also because they are exposed to many risk factors. The aim of this study was to evaluate the prevalence of orofacial injuries, militaries knowledge about first-aid procedures following a dental avulsion and the use of mouthguards in a sample of Portuguese militaries. Materials and Methods: An observational cross-sectional study was conducted for forces of the Infantry Regiment n°14 of Viseu, Portugal. The study involved 122 members of the armed forces who were asked to complete a questionnaire, which enquired about: the occurrence of dental trauma, the use of mouthguards and militaries knowledge with regard to first-aid management of dental avulsions. Results: In our sample, 5.7% reported having experienced a dental trauma. This was further broken down to reveal that 2.5% had experienced an avulsion and 3.3% had a dental fracture. All respondents who reported having suffered dental trauma, reported that this was the only time that they had experienced dental trauma. Within this group, 71.4% visited a dentist, however only one (20%) visited the dentist during the same day that the trauma occurred. In addition, 21.3% mentioned that they had seen a dental trauma in at least one colleague during military trainings/operations. In the case of dental avulsion, the majority (54.9%) did not know how to act. The rate of mouthguard's use among militaries was very low (6.4%). The main reason reported for not using a mouthguard was thinking that it is not necessary (53.3%). Besides that, 31.1% did not know what a mouthguard was for. Conclusion: Prevention programs and promoting actions with this population are important reflections and should be adopted to reduce the incidence of orofacial trauma and to increase knowledge about this topic.